Wheat bran biorefinery – An insight into the process chain for the production of lactic acid. (March 2015) - Tirpanalan, Özge; Reisinger, Michael; Smerilli, Marina; Huber, Florian; Neureiter, Markus; Kneifel, Wolfgang; Novalin, Senad
Highlights: A wheat bran biorefinery concept including the major processing steps was studied. A pre-extract containing 32% of the total dry mass was obtained. Fermentation of lignocellulosic fraction yielded 0.73 g lactic acid/g substrate. An overall product efficiency of 47% was achieved experimentally. A maximum product yield of 80% could be estimated theoretically. Abstract: The present study investigates a wheat bran biorefinery including major processing steps pre-extraction, pre-treatment and lactic acid fermentation. Concerning the dry mass distribution, during the pre-extraction 32% of the feedstock was recovered, offering some perspectives for applications in food area. The pre-treatment (hydrothermal/enzymatic hydrolysis) of the remaining cake solubilized 34% of dry mass and led to a fermentable sugar concentration of 21 g/L. The fermentation resulted in a lactic acid yield of 0.73 g/g substrate. Concentrating the fermentation feed via nanofiltration did not improve the lactic acid productivity. Taking into account that Lactobacillus pentosus, a heterofermentative microorganism was used, the dry mass balance revealed a product yield of 47% (32% extract, 15% lactic acid). Based on a theoretical consideration involving a cellulolytic enzyme production (10% feedstock allocation) and lignin utilization, under optimized conditions a maximum product yield of around 80% (35% extract, 39% lactic acid, 6% lignin) could be expected.